Optimizing the establishment of bean and maize varieties in tropical environments. Issue 1 (September 2021) - Andrade, J A; Mateus, M; Cadima, J F; Abreu, F G
Abstract: The successful establishment of any crop is the initial indication of its productivity. Optimizing the establishment of a crop implies ensuring generalized, fast and concentrated emergence. This work studies optimal temperature ranges, under non-limiting water conditions, for both germination and emergence of two bean ( Phaseolus vulgaris L.) varieties ( catarina and ervilha ) and two maize ( Zea mays L.) varieties ( matuba and sam3 ). Experiments used a thermogradient plate. Petri dishes were used for germination experiments. Emergence experiments were performed in aluminium containers filled with packed portions of a sandy loam clay textured soil. Size, speed and spread of both germination and emergence were measured at different temperatures by Cu-CuNi thermocouples. Thermal ranges with optimal counts of both germination and emergence [To1 sz, To2 sz ] were identified using a flattened bell curve function. Speed was maximized for either germination or emergence over thermal ranges [To1 sp, To2 sp ] defined using the plateau model to relate either germination or emergence rates with temperature. Ranges along which the spread of both germination and emergence are nearly minimized [To1 sd, To2 sd ] were identified with the aid of even-degree polynomials. The intersection of all three thermal ranges gave rise to optimal temperature ranges [To1, To2 ] for germination (OTRG ) of the four varieties in study and for emergence (OTRE ) of three of them. In general, the lower thermal limit of OTRg was determined by speed (To1 = To1 sp ) and the upper thermal limit by size (To2 = To2 sz ). OTRe begins at To1 sp for ervilha and sam3 and at To1 sd for catarina and ends at To2 sz for catarina and at To2 sd for the others. The endpoints and length of both the OTRG and OTRE were also found to be crop-dependent. Thus, farmers can choose between crops and optimize their establishment. The identification of these parameters may also be useful in assessing weather forecasts and for warning systems and agro-climatic zoning. The influence of the substrate used in each experiment was also discussed.